PERSEPSI MAHASISWA TERHADAP ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN BAHASA INDONESIA - Vioni Saputri; Ilham Abdi Prawira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The emergence of technological innovation provides new things that can strive for ease in life. The topic that is currently trending is inseparable from AI (Artificial Intelligence). A program that has been used in various sectors whose goal is to replace all jobs, such as humans. Represented by thought and intelligence by design connecting information that resembles a human. This research aims to explain the use of AI and students' perception of AI in Indonesian language learning. Using qualitative research methods is phenomenological. The results of this research are 1) Utilization provided through the ease of learning resources, fulfillment of helpful tasks in terms of flexibility, and providing feedback. 2) Students' perception of AI in Indonesian learning is influenced by positive and negative perceptions, influencing factors, the desired attitude of students in its use, and recommendations from related parties. In conclusion, the study of AI is centered on the dimension of world culture that contributes to the advancement of knowledge, but has a diverse impact on the implementation of each actor who uses it.